Economic and Environmental Impacts of Electric Vehicle Society in Toyohashi City in Japan - A CGE Modeling Approach - - Yuzuru Miyata; Hiroyuki Shibusawa; Tomoaki Fujii (European Regional Science Association (ERSA), 2014)
In this paper we explore economic and environmental impacts of promotion and realization of an electric vehicle society (EVS). More concretely, this paper emphasizes a CGE-modelling approach to evaluate the following issues: entire economic impacts of subsidies for promotion of an EVS, the possibility of carbon dioxide (CO2) emissions and prices reduction, a change of industrial structure towards an EVS, and a modal shift towards an EVS. Our simulation results demonstrate that after applying 20% subsidies to five industries including electric vehicles (EVs) manufacturing, EV transport, solar power generation, cogeneration and other transport, the total industrial output and municipal GDP increase. A large growth rates are found in industries where subsidies are introduced except non-ferrous metal industry. However, it is motivating that decreasing proportions are found in oil, coal product, mining, heat supply and gasoline vehicles (GVs) transport industries. Moreover all the commodity prices decrease since subsidies are given to some industries. Hence Toyohashi Cityfs economy shows a direction where the demand for conventional vehicles and energy use are decreased, conversely, the demand for EVs and renewable energy are increased that displays different lifestyles from the current one. For all these reasons, it is our conclusion that EVS can really represent a realistic and alternative society both in terms of economic development and CO2 emissions reduction. In this study therefore it is clear that modal shift will occur to EVS, and thus we suggest for promotion of a new industrial structure to introduce an EVS in Toyohashi City in Japan. The proposed model can even be applied to the other cities in Japan and other countries in the world which are similar to this area.
Keywords: 330; electric vehicle; CGE; Toyohashi; R13; O18